Microporous framework solids - Wright, Paul A. (RSC materials monographs., 2008)
"Microporous Framework Solids describes fundamental principles and experimental practices of the synthetic chemistry and physical characterisation of crystalline microporous solids. It also provides a clear and up to date discussion of different types of microporous materials, their applications and emerging areas of current interest, written from a personal research perspective." "Topics include the different types of solids and their properties with key emphasis placed on the relationship between properties and structure. Structural methods are also discussed including the role of diffraction, NMR and computational studies. Finally, applications for catalysis are reviewed." "This book is ideal for new researchers in the field of microporous solids both in academia and industry who require a detailed and informative overview of the subject. It provides a comprehensive review of microporous materials in an easily accessible style offering a valuable source of references over a wide range of topics."--BOOK JACKET.